Navigation, sea, and impressions of the Adriatic in the memoirs of a Russian officer - N. Cabassi (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper intends to investigate human events and natural phenomena, focusing in particular on the sea and atmospheric conditions faced by D.N. Senyavin's crew during the expedition to the Adriatic Sea in the first half of the year 1806. The study has been carried out based on the data of the memoirs of V.B. Bronevskii, a second lieutenant of the Russian Navy who took part in the expedition, published in 1836 – 1837. The narration covers different levels: on one hand, the diary is a precious source of events and echoes of history; on the other hand, the author's voice emerges in the generous descriptions of the geographic-naturalistic horizon, in the stories with an ethnographic, botanical, physical, artistic, human and psychological taste, coming out in his sailing tales. The diary, therefore, turns up to be worth not only in its documentary and historical source, but rather in its literary and ethnographic pages. The search leads to the conclusion that sailing is a revealing experience of life in all its manifestations and that sea is a mystery of true knowledge, misterium cognitionis, for the author.